Mention of Vasyl Karazin on the pages of the Ukrainian newspaper "Svoboda" in the USA. - Grinchenko , Victor (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
The aim of the study. Highlight and analyze diverse information about the life and activities of Vasyl Nazarovych Karazin (1773–1842) as reflected throughout the pages of the Ukrainian newspaper Svoboda published in the USA.Research methodology. The principles of historicism, objectivity, comprehensiveness and integrity in study of the source, as well as the approaches used in modern biographical studies, are applied. Methods used: descriptive, analysis and synthesis, historical and comparative, historical-biographical, prosopographical.Academic novelty. The materials presented in this publication can serve as a certain supplement to existing studies in highlighting the historiographical image of Vasyl Karazin in the intellectual environment of the Western Ukrainian diaspora.Conclusions. It has been established that publications presenting facts and analytical judgments about the life and activities of V. N. Karazin, which varied in scope and content, were printed in the Ukrainian newspaper Svoboda published in the United States, starting from the mid-1930s until the beginning of the 21st century. The relevant materials mainly reflected the tendency to evaluate him as a prominent and conscious Ukrainian, the “architect” of the Ukrainian Revival, who in every way sought to work for the good of Ukraine, trying to direct it to the European path of development. There are good reasons to believe that this position exerted a dominant influence on the formation of the image of Vasyl Karazin among the readers of the Svoboda newspaper in the USA as part of the Ukrainian diaspora community. The point of view of the authors who stuck to somewhat different views and attributed only regional, Sloboda Ukrainian patriotism to V. N. Karazin, was mentioned only in passing.